The Influence of Traditional Games on Improving Physical Fitness of Class VI Students at SD Negeri 70 Palembang - Oktarina, Oktarina; Manullang, Jujur Gunawan; Imansyah, Farizal (Perkumpulan Program Studi Doktor Pendidikan (PPSDP), 2024)
Physical fitness is the body’s ability to carry out daily activities without feeling excessive fatigue. So, someone with good physical fitness will always have enough energy to carry out physical activities smoothly. Improving physical fitness can be helped with several games, one of which is traditional games. By providing traditional games, including GalahAsin, UcingBaledog, Jump Rope and Oray-Orayan, elementary school students could improve their physical fitness. The aim was to determine the effect of traditional games on improving the physical fitness of class VI students. This research used an experimental method using a One-Group Pretest-Posttest research design with a research population of 30 Class V students using a saturated sampling technique including 14 male and 16 female students. The research instrument that the author used was the TKJI test. With the research results, the magnitude of the effect between the pre-test and the post-test was 0.593, x 100% = 59.3%. This shows that each participant was able to show an increase of 59.3% from the pre-test results to the post-test. This means that traditional games can increase the physical fitness of each participant by 59.3%. So, it can be concluded that traditional games have an influence on the physical fitness of class VI students. So, the use of traditional games was suitable for improving the physical fitness of class VI students at State Elementary School 70 Palembang.